Economic Policy Uncertainty and Cost of Debt Financing in Indonesia - Komari, Nadya; Juliana, Rita (E-Jurnal Akuntansi, 2022)
This study aims to see the effect of Economic Policy Uncertainty (EPU) to the cost of debt in Indonesia. This quantitative research sample used in this study includes a total of 4,312 observations collected from 453 listed firms on IDX from the period 2006 to 2020. Using fixed-effect panel data regression, our result shows that there is a positive relationship between the cost of debt and EPU, and the effect is even greater when a crisis occurs. With additional analysis conducted, our result show EPU has stronger impact on large firms’ than small firms’ cost of debt. However, when a crisis occurs, EPU has a higher effect on small firms samples than on large firms samples. Thus, it can be concluded if the crisis plays an important role in the research results. Keywords: Cost Of Debt; Economic Policy Uncertainty; Crisis.